Effect of varying component reliabilities on system reliability in flange-angle partially restrained steel moment connections - Bhattacharya, Baidurya; Chatterjee, Aritra; Chakravorty, Trisha; ICASP14 (My University, 2023)
Load paths of lateral moment-resisting frames involve steel moment connections comprising several components such as angles, plates, bolts and welds. As per codal provisions, each component is designed on the basis of its individual limit state. However, there has not been much focus on system reliability of the connection as a whole, which represents the true measure of its performance. Connection systems are neither purely series nor parallel systems. Much of the mechanics still remain undiscovered, as does the comprehensive set of limit states that could potentially contribute to system failure. This paper proposes a methodology to estimate system reliability of steel connections designed using component-based codal provisions. Specifically, we take up the flange-angle partially restrained connection configuration that connects a beam to a column with top and bottom seat angles bolted to beam flange and column flange. The load sharing network topology of the connection system is presented in the form of a fault tree including all possible modes of failure. Apart from the four reliability elements recognized by standardsﾗshear in beam-flange bolts, tension in column-flange bolts, tension in horizontal and flexure in vertical leg of angleﾗtwo additional limit states are identified: angle corner flexure and tension in beam-flange bolts. Geometric and material nonlinear finite element analysis is performed on various combinations of diameters of beam-flange and column-flange bolts. Flexural demand is increased monotonically up to failure to obtain moment-rotation curves and governing limit states. System parameters (beam-flange and column-flange bolt diameters) are modified such that the analysis captures the (random) most critical limit state for system failure initiation. Stochastic simulations are performed to obtain sets of moment-carrying capacities which are convolved with an assumed load distribution curve to estimate system reliability. A three-dimensional system reliability surface is plotted with component reliabilities of beam-flange bolts and column-flange bolts and system reliability on the three axes. System reliability surfaces could be used to optimize component reliabilities using a system reliability sensitivity algorithm such that a target system reliability is achieved. The results of this paper suggest that current standards may be oversafe. The methodology could potentially be applied to different connection topologies used in practice to update component design provisions and modify partial safety factors against a target system reliability, which could someday be incorporated into design standards.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED